(untitled) (Almanack, 2021)
One of the puzzling questions about the formal Dutch abolition of the slavetrade in 1814 is why a state that was so committed to maintaining slavery in its Empire did not put up any open resistance to the enforced closing of the trade that fed it. The explanations that historians have given so far for this paradox focus mainly on circumstances within the Netherlands, highlighting the pre-1800 decline of the role of Dutch traders in the African slave-trade, the absence of a popular abolitionist movement, and the all-overriding focus within elite-debates on the question of economic decline. This article argues that the (often partial) advanced made by abolitionism internationally did have a pronounced influence on the course of Dutch debates. This can be seen not only from the pronouncements by a small minority that advocated abolition, but also in the arguments produced by the proponents of a continuation of slavery. Careful examination of the three key debates about the question that took place in 1789-1791, 1797 and around 1818 can show how among dominant circles within the Dutch state a new ideology gradually took hold that combined verbal concessions to abolitionist arguments and a grinding acknowledgement of the inevitability of slave-trade abolition with a long-term perspective for prolonging slave-based colonial production in the West-Indies.